Enhanced light harvesting of dye-sensitized solar cells with up/down conversion materials. (1st February 2015) - Yao, Nannan; Huang, Jinzhao; Fu, Ke; Deng, Xiaolong; Ding, Meng; Shao, Minghui; Xu, Xijin
Abstract: Rare-earth doped ZnO up/down-conversion materials were prepared and introduced into photoelectrodes to enhance the photovoltaic efficiency of dye-sensitized solar cells. In this paper, we achieved a optimal efficiency of 5.13% with the incorporation of ZnO:Eu 3+, Tb 3+ and ZnO:Er 3+, Yb 3+, which is about 70% higher than that of dye-sensitized solar cells based on pure TiO2 . This is probably due to the enhancement of light harvesting via converting ultraviolet and near infrared radiation to visible emission by downconversion and upconversion luminescence process, respectively. In addition, the ZnO:Eu 3+, Tb 3+ film acted as a blocking layer inhibit the charge recombination, suppressing the dark current for DSSCs. Results indicate that the ZnO:Eu 3+, Tb 3+ /TiO2 :ZnO:Er 3+, Yb 3+ double composite layers can obviously improve the efficiency of dye-sensitized solar cells, and the combine of the up and down conversion materials is an effective method to extend the response both to ultraviolet and near-infrared radiation in dye-sensitized solar cells.